2020
DOI: 10.1155/2020/4321912
|View full text |Cite
|
Sign up to set email alerts
|

CD137 Signaling Promotes Endothelial Apoptosis by Inhibiting Nrf2 Pathway, and Upregulating NF-κB Pathway

Abstract: Background. Endothelial dysfunction and apoptosis resulting from oxidative stress can lead to the development of atherosclerosis. Our group has previously showed that CD137 signaling contributes to the progression of atherosclerosis and the vulnerability of plaques. The aim of this study is to investigate the effects of CD137 signaling in atherosclerosis on endothelial cells (ECs) apoptosis and to explore the underlying mechanisms. Methods. Serum samples were collected from 11 patients with acute myocardial in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Studies have suggested that CD137 can play a critical role in the development of atherosclerosis because our previous research has indicated that it can promote the formation of intraplaque calcification and neovascularization in atherosclerosis, leading to an increased risk of plaque rupture. [23][24][25][26][27][28][29][30] However, the role of CD137 in MI has not been clearly elucidated. Analysis of transcriptional data from myocardial fibroblasts isolated after MI indicates that CD137 is the primary inflammatory pathway activated on the first day after MI, suggesting that CD137 signaling activation on myocardial fibroblasts may play a role in the process of fibroblast phenotype transformation and MI.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that CD137 can play a critical role in the development of atherosclerosis because our previous research has indicated that it can promote the formation of intraplaque calcification and neovascularization in atherosclerosis, leading to an increased risk of plaque rupture. [23][24][25][26][27][28][29][30] However, the role of CD137 in MI has not been clearly elucidated. Analysis of transcriptional data from myocardial fibroblasts isolated after MI indicates that CD137 is the primary inflammatory pathway activated on the first day after MI, suggesting that CD137 signaling activation on myocardial fibroblasts may play a role in the process of fibroblast phenotype transformation and MI.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups of genes that implicated in apoptosis, calcium regulation and cell cycle checkpoints were found and were validated using quantitative PCR. The most significantly up-regulated gene after tanshinone IIA treatment was TNF receptor superfamily member 9 (TNFRSF9, also known as CD137), which is primarily involved in apoptosis and inflammation ( 37 , 38 ). Research studies have shown that TNF-α, the receptor of which is a homologous to TNFRSF9, is able to induce two distinct caspase-8 activation pathways ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, reactive oxygen species upregulate proapoptotic proteins, such as Bax and cleaved caspase‐3, and downregulate antiapoptotic proteins, such as Bcl2, thereby inducing EC apoptosis. 25 The mechanism underlying the effects of CD137 signaling on human umbilical vein endothelial cells also includes the diacyl glycerol–PKC (protein kinase C) signaling pathway. Stimulation of human umbilical vein endothelial cells with anti‐CD137 antibody leads to the rapid formation of inositol triphosphate, which in turn upregulates diacyl glycerol levels and PKC activity and consequently results in the translocation of PKC from the cytosol to the plasma membrane.…”
Section: Role Of Cd137 In Vascular Disordersmentioning
confidence: 99%